ANALISIS DAN PERANCANGAN APLIKASI E-LIBRARY SEKOLAH BERBASIS WEB MENGGUNAKAN METODE SCRUM - Abimayu, Fajri; Simanjuntak, Pastima (Computer Science and Industrial Engineering, 2023)
With advances in information technology, searching and accessing data can be done quickly, efficiently and accurately, one of which is in the library. With current technological developments, it is necessary to have an information system that handles library administration. The information system is related to book data management, member data management, book lending circulation data management. Likewise with cases of problems experienced with the Batam 19 State High School library system. However, so far the library at SMA N 19 Batam still uses a manual management system with all book borrowing transaction processes written in an archive. The lack of use of technology to facilitate access and management of the library at the school can result in too much data being entered using paper and making it difficult for librarians to manage it. Thus causing the level of accuracy of search and storage to be less attention. Therefore researchers are interested in conducting research entitled "Analysis and Design of Web-Based School E-library Applications Using the Scrum Method", to improve the quality and efficiency of designing e-library applications in meeting the needs of the SMA N 19 Batam library. Keywords: scrum methods, e-library, web based.